ECTHR_COMMITTEE 47008/12 vom 16. Juli 2015 , AFFAIRE ALEXIOU c. GRÈCE - Ecthr Committee (2015)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure administrative;Article 6-1 - Délai raisonnable); Violation: 6;6-1